Alcohol use in times of the COVID 19: Implications for monitoring and policy. (2nd May 2020) - Rehm, Jürgen; Kilian, Carolin; Ferreira‐Borges, Carina; Jernigan, David; Monteiro, Maristela; Parry, Charles D. H.; Sanchez, Zila M.; Manthey, Jakob
Abstract: Based on a literature search undertaken to determine the impacts of past public health crises, and a systematic review of the effects of past economic crises on alcohol consumption, two main scenarios—with opposite predictions regarding the impact of the current COVID‐19 pandemic on the level and patterns of alcohol consumption—are introduced. The first scenario predicts an increase in consumption for some populations, particularly men, due to distress experienced as a result of the pandemic. A second scenario predicts the opposite outcome, a lowered level of consumption, based on the decreased physical and financial availability of alcohol. With the current restrictions on alcohol availability, it is postulated that, for the immediate future, the predominant scenario will likely be the second, while the distress experienced in the first may become more relevant in the medium‐ and longer‐term future. Monitoring consumption levels both during and after the COVID‐19 pandemic will be necessary to better understand the effects of COVID‐19 on different groups, as well as to distinguish them from those arising from existing alcohol control policies.